A study in scene shaping: Adjusting F-formations in the wild - Bohus, Dan; Andrist, Sean; Horvitz, Eric (2017 AAAI Fall Symposium: Natural Communication for Human-Robot Collaboration, 2017)
We study the automated shaping of F-formations in the proximity of a stationary robot that has been deployed to provide directions within a building. We introduce the notion of scene shaping where suboptimal spatial configurations are detected and desired shifts in the locations of participants and bystanders are communicated with natural language and gestures. We conduct an initial in-the-wild study with the proposed methods and report results, lessons learned, and future directions of research.